SCIENTIFIC COMMUNICATION SKILLS ARE IMPORTANT FOR ALL CLINICIANS - A. Yu. Gasparyan (Научно-практическая ревматология)
The author discusses the need for scientific communication, knowledge about impact indicators and other criteria for assessing scientific publications, as well as current approaches to choosing journals to publish the results of researches. The high level of Russian rheumatology and the quality of articles published in the journal «Nauchno-Prakticheskaya Revmatologiya» (Rheumatology Science and Practice) are mentioned.